Reinterpretasi Makna Terang Berdasarkan Matius 5:14-16 dan Implikasinya Bagi Panggilan Orang Kristen Di Dunia Kerja - Purba, Eli Brigita; Jonathans, Kornelius Rulli; Nugrosho, Andreas Eko (Jurnal Teologi Cultivation, 2025)
This article examines the Calling of Christians in their duties and responsibilities to be Light in the workplace world. Discussing the Biblical understanding of the concept of Light as an Interpretation of the Identity of Christians in their duties and responsibilities in the Workplace world. Christians as representatives of God are entrusted with the mandate to have an impact on the work environment, so that they become a testimony to many people and through them the name of God is glorified. This scientific paper uses a qualitative research method that is an exegetical study of the Bible text regarding the Meaning of Light as a Reinterpretation of the Calling for Believers in the workplace world. This study uses a Contextual, Grammatical or grammatical and Historical approach to the text of Matthew 5:14-16. This section also describes the Principles and values of truth from the Bible text related to the Calling of Christians to be Light in the workplace environment so that it can help them to realize and position their identity as a Reflection of the Light of Christ through their lives. The results of the study show an understanding of the concept of Self-Identity and the Calling of Believers as the Light of Christ in the Workplace world so that they as the Light have a great impact in the workplace world to become witnesses to the glory of Christ, so it can be concluded that the Reinterpretation of the Meaning of Light based on Matthew 5:14-16 has implications for the Calling of Christians in the Workplace Environment